The Role of Nanocoating and Fluid PH Level on the Enhancement of Surface Hydrophobicity Behavior. Issue 1 (2017) - Ali, Naser; Teixeira, Joao; Addali, Abdulmajid; Shaban, Feras Al-Zubi and Ehab
No abstract available